A meta-analysis of the effects of UV radiation on the plant carotenoid pool - Badmus, Uthman O; Ač, Alexander; Klem, Karel; Urban, Otmar; Jansen, Marcel A K (Plant physiology and biochemistry, 2022)
Induction of metabolite biosynthesis and accumulation is one of the most prominent UV-mediated changes in plants, whether during eustress (positive response) or distress (negative response). However, despite evidence suggesting multiple linkages between UV exposure and carotenoid induction in plants, there is no consensus in the literature concerning the direction and/or amplitude of these effects. Here, we compiled publications that characterised the relative impact of UV on the content of individual carotenoids and subjected the created database to a meta-analysis in order to acquire new, fundamental insights in responses of the carotenoid pool to UV exposure. Overall, it was found that violaxanthin was the only carotenoid compound that was significantly and consistently induced as a result of UV exposure. Violaxanthin accumulation was accompanied by a UV dose dependent decrease in antheraxanthin and zeaxanthin. The resulting shift in the state of the xanthophyll cycle would normally occur when plants are exposed to low light and this is associated with increased susceptibility to photoinhibition. Although UV induced violaxanthin accumulation is positively linked to the daily UV dose, the current dataset is too small to establish a link with plant stress, or even experimental growth conditions. In summary, the effects of UV radiation on carotenoids are multifaceted and compound-specific, and there is a need for a systematic analysis of dose-response and wavelength dependencies, as well as of interactive effects with further environmental parameters.
Keywords: rostliny; Ultraviolet Rays; Zeaxanthins; zeaxanthiny; ultrafialové záření; UV; Carotenoids; karotenoidy; Plants; Meta-Analysis; Acclimation; Xanthophyll cycle